Exploring User Experience of Wayfinding in a Large and Complex Hospital - Kim, M.; Han, S.; Wang, Xiangyu (National Taiwan University Press, Taiwan, 2012)
Wayfinding is a very complicated perceptual and cognitive process, especially in large and complicated environments such as hospitals and big shopping centers. Many studies show inhabitants of large environments can become lost very easily if they are unfamiliar with the environment. Although they may eventually be able to find a target location, it is very time-consuming to consult a map, understand the signs, and ask people for directions. This research identified factors that influence wayfinding and developed a customized questionnaire with a focus on user experience of wayfinding: generating an environmental image of the lobby, identifying information factors, understanding environmental factors, and linking environmental factors with information factors. An explorative study was conducted to investigate user experience of wayfinding in a large hospital, where the application of the questionnaire was validated in a real-life situation. The results show that participants experienced difficulties in generating a clear image of the lobby, identifying wayfinding aids, and understanding some of the information provided by the wayfinding aids. Further, there was no portable and continuous wayfinding service, which caused problems in recalling the information learned from the wayfinding aids, especially when attempting to return to the lobby. The potential of mobile AR for wayfinding aids is presented as an implication from the results of the explorative study, and the technological framework of the mobile AR wayfinding aid and its implementation in hospitals is proposed for future study.